One patient with Sjogren’s syndrome presenting schizophrenia-like symptoms - Lin C (Neuropsychiatric Disease and Treatment)
Ching-En Lin1,2 1Department of Psychiatry, Taipei Tzu-Chi Hospital, Buddhist Medical Foundation, Taiwan, Republic of China; 2School of Medicine, Tzu-Chi University, Hualien, Taiwan, Republic of China Abstract: Comorbid depression in patients with Sjogren’s syndrome has been reported frequently, while comorbid psychosis in subjects with Sjogren’s syndrome has rarely been reported. Here we report a patient with Sjogren’s syndrome who presented with schizophrenia-like symptoms such as persecutory delusions and auditory hallucinations in contrast to her previous psychiatric presentations, which only included depression and anxiety. Keywords: mental illness, psychosis, Sjogren’s syndrome, schizophrenia